Kontekstualisasi Pemikiran Pendidikan Muhammad Iqbal dalam Pembelajaran Pendidikan Agama Islam (PAI) - Nurhidin, Edi (Jurnal al Hikmah, 2017)
A theory is only be a knowledge without application. It is also Muhammad Iqba>lâs education theory. Many people study that theory in various way, but little people know how to practice it. Therefore this article try to reveal how to practice Iqba>lâs education theory in the Islamic education learning in the school. As the outline of Iqbalâs education theory, the contain of this theory is about education goal, maximize individual potency of every student. To reach the goal, it need society participation, make student be subject of study and disappear religious knowledge and science dichotomy. Therefore the suitable learning model for Muhammad Iqba>l education theory is student-centered learning model which student is thought as learning subject, so student can maximize their potency